Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3390/ijms151223141
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Pathogen Interaction, Circadian Rhythm, and Hormone-Related Gene Expression Provide Indicators of Phytoplasma Infection in Paulownia fortunei

Abstract: Phytoplasmas are mycoplasma-like pathogens of witches’ broom disease, and are responsible for serious yield losses of Paulownia trees worldwide. The molecular mechanisms of disease development in Paulownia are of considerable interest, but still poorly understood. Here, we have applied transcriptome sequencing technology and a de novo assembly approach to analyze gene expression profiles in Paulownia fortunei infected by phytoplasmas. Our previous researches suggested that methyl methane sulfonated (MMS) could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…Leaf color is related to chloroplast development, the size and number of chloroplasts, and the production of photosynthetic pigments. Fan et al [42] also found the genes which encode PIF3 involved in light signal transduction. PIF3 takes effect in the response of Paulownia in abiotic stresses and is involved in biosynthesis and signaling pathways of hormones including brassinosteroids, GA, and abscisic acid [47].…”
Section: Relationship Between As and The Paulownia Plants Responses Tmentioning
confidence: 98%
See 1 more Smart Citation
“…Leaf color is related to chloroplast development, the size and number of chloroplasts, and the production of photosynthetic pigments. Fan et al [42] also found the genes which encode PIF3 involved in light signal transduction. PIF3 takes effect in the response of Paulownia in abiotic stresses and is involved in biosynthesis and signaling pathways of hormones including brassinosteroids, GA, and abscisic acid [47].…”
Section: Relationship Between As and The Paulownia Plants Responses Tmentioning
confidence: 98%
“…MYC2 is the positive regulation factor mediated by JA in regulating the inhibition of stem elongation and tolerance of plants to oxidative damage. In previous studies, the MYC2 which was related to plant-pathogen interactions was identified [42]. When the JA concentration is high, JAZs are degraded, leading to MYC2 being released to promote the JA regulation of plant growth.…”
Section: Degs Related To Phytohormonesmentioning
confidence: 99%
“…The involvement of ARFs in response to biotic stresses was also revealed in Arabidopsis thaliana [60], Gossypium [61] and Oryza sativa Linn [62]. In addition, Fan et al [63] suggested that the concentration of Indole-3-acetic acid (IAA) in PaWB-infected plants was significantly lower than that in healthy plants, while the concentration of cytokine (CK) in PaWB-infected plants was significantly higher than that in healthy plants. Moreover, the upregulation of CK/IAA could lead to the appearance of witches' broom symptoms.…”
Section: Pawb Responsive Der-target Gene Pairs Regulate Morphologicalmentioning
confidence: 99%
“…Witches' broom disease occurs in many countries and is the biggest threat to Paulownia production, causing serious economic losses [1,2]. In Paulownia, witches' broom disease has been found in saplings and big trees, and leads to malformations of branch, leaf, stem, and flower, such as witches' broom, yellowing, phloem necrosis, and phyllody, respectively [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Rifampicin treatment can make PaWB-infected Paulownia recover to normal morphology [13]. Furthermore, the rapid development of 'omics' has allowed for the investigation of the transcriptomes [3,[14][15][16][17][18], microRNAs (miRNAs), degradomes [19][20][21][22], and proteomes [4,23] of Paulownia species, and the results have revealed changes after PaWB infection at transcriptional, post-transcriptional, and translational levels.…”
Section: Introductionmentioning
confidence: 99%